Sistem Informasi Akuntansi Penyusutan Aktiva Tetap Dengan Metode Garis Lurus Pada SMK Muhammadiyah 1 Weleri berbasis Web - Ahmad Asifuddin; Haris Ihsanil Huda; Zaenal Mustofa (Elkom : Jurnal Elektronika dan Komputer, 2021)
Information technology is a technology used to process data, including processing, obtaining, compiling, storing, manipulating data in various ways to produce relevant, accurate and timely information, which is used for personal, business and government purposes and is strategic information for decision making, in recording fixed assets for example, must be managed properly because the need for the data is frequent intensity, the number of items is not small so it is impossible to memorize, the calculation of depreciation of fixed assets of a company needs to be done at the end of every year because it will affect the book value and depreciation expense on the balance sheet and depreciation expense on fixed assets on the income statement. This depreciation calculation can also be used as a reference in the allocation to purchase new assets if the existing fixed assets can no longer be used. Obstacles in preparing depreciation reports if not resolved immediately will have a bad impact on schools, for example being late in submitting annual tax reports due to the long preparation of depreciation reports will result in schools being fined for being late in reporting the annual corporate tax return. With the accounting information system for depreciation of fixed assets, it is expected that it will facilitate officers in managing fixed asset data and depreciation reports. The new system that will be designed is web-based, so that it can be accessed at any time by interested parties and makes coordination time more effective.